Accounting Treatment of Defective Products at MSMEs in Sidoarjo: Perlakuan Akuntansi Terhadap Produk Cacat pada Umkm di Sidoarjo - Inta Rifana; Santi Rahma Dewi (Universitas Muhammadiyah Sidoarjo, 2021)
The main purpose of establishing a business is to earn profits and have a quality product. Companies usually experience problems in the production process, one of which is getting products that do not meet production quality standards, such as obtaining defective products. The purpose of this study is to find out how the accounting treatment of defective products is applied by MSMEs in Sidoarjo and to find out how the impact of defective products on the cost of production of MSMEs in Sidoarjo. This type of research uses a qualitative descriptive approach. The data used are primary data and secondary data with data collection techniques namely observation, interviews, literature study and documentation. This research was conducted by surveying the research location and then conducting interviews and analyzing company data in the form of reports on raw material purchases, sales report data, goods production data for January 2021, product unit price report data, product report data for both defective products and defective product data on January 2021, the cost of production.